The Routledge companion to children's literature - Rudd, David, 1950- (Abingdon, Oxon. ; New York : Routledge, 2010)
The Routledge Companion to Children's Literature is a vibrant and authoritative exploration of children's literature in all its manifestations. It features a series of essays written by expert contributors who provide an illuminating examination of why children's literature is the way it is.-publisher description.
Development of children's literature / David Rudd -- 'Criticism is the theory of literature' : theory is the criticism of literature / Roderick McGillis -- Gender studies / Victoria Flanagan -- Race, ethnicity and colonialism / Clare Bradford -- Narratology / John Stephens -- Realism / Lucy Pearson and Kimberley Reynolds -- Fantasy / Karen Coats -- Young adult fiction and the crossover phenomenon / Rachel Falconer -- Picturebooks, comics and graphic novels / Mel Gibson -- Media adaptations / Margaret Mackey -- Sidelines : some neglected dimensions of children's literature and its scholarship / Evelyn Arizpe and Morag Styles with Abigail Rokison.
Includes bibliographical references (pages 279-305) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Children's literature -- History and criticism -- Handbooks, manuals, etc; Children -- Books and reading -- Handbooks, manuals, etc; Electronic books